Protein-glycan interactions - Prestegard, James (Henry Stewart Talks, 2012)
NMR studies, Protein structure, Protein-protein Interactions, Building models with a ligand, Chemokine CCL5 interactions with GAGs, STD-NOESY, Residual dipolar coupling (RDC), SAXS data, Cross-saturation, Radical footprinting, Glycans on a glycoprotein, - Preparing IgG with homogeneous 13C glycans, Relaxation dispersion, Galactose terminated Fc glycans Locating glycans more precisely, Sialylated glycans, CPMG R2 relaxation, Di-sialylation